Long-Term Safety and Efficacy of Dolutegravir in Treatment-Experienced Adolescents With Human Immunodeficiency Virus Infection: Results of the IMPAACT P1093 Study. (5th April 2019) - Viani, Rolando M; Ruel, Theodore; Alvero, Carmelita; Fenton, Terry; Acosta, Edward P; Hazra, Rohan; Townley, Ellen; Palumbo, Paul; Buchanan, Ann M; Vavro, Cindy; Singh, Rajendra; Graham, Bobbie; et al.
Abstract: Background: P1093 is an ongoing phase I/II multicenter open-label study of dolutegravir plus an optimized background regimen in age-defined pediatric cohorts; here we report the long-term safety and virologic efficacy outcomes for the oldest cohort. Methods: The study enrolled human immunodeficiency virus type 1 (HIV-1)–infected treatment-experienced adolescents aged 12 to <18 years, with an HIV-1 RNA level ≥1000 copies/mL . Cumulative safety and HIV-1 RNA outcomes were assessed once the last enrolled participant reached 144 weeks of follow-up. Results: Among 23 adolescents enrolled, 16 remained in the study at least 144 weeks; the median follow-up was 153 weeks (range, 55–193 weeks). Dolutegravir was well tolerated, with grade 3 clinical adverse events in 5 participants, grade 3 laboratory abnormalities in 3, and grade 4 laboratory abnormalities in 1; none of the adverse events or abnormalities were judged to be treatment related. In an-intent-to-treat analysis, an HIV-1 RNA level <400 copies/mL at week 144 was achieved in 43% (10 of 23 participants; 95% confidence interval, 23.2%–65.5%); in addition, 35% (8 of 23; 16.4%–57.3%) had an HIV-1 RNA level <50 copies/mL. Nine participants (39%) discontinued study treatment before 144 weeks, but none because of adverse events or drug intolerance. All participants with sustained virologic control had excellent adherence; most who experienced virologic failure had adherence levels <90%. HIV-1 genotypic drug resistance testing was available at time of failure from 6 participants; 1 had evolution in integrase resistance with E138T, S147G, and R263K mutations at week 192 and phenotypic dolutegravir resistance of a 5.1-fold change. Conclusions: Dolutegravir plus an optimized background regimen seemed safe, well tolerated, and efficacious in this cohort of treatment-experienced HIV-1-infected adolescents. Adherence remains problematic in this population. Clinical Trials Registration: NCT01302847. Abstract : The phase I/II P1093 study enrolled treatment-experienced human immunodeficiency virus–infected adolescents, followed up for a median of 153 weeks. Dolutegravir plus an optimized background regimen was safe, well tolerated, and efficacious for those who adhered to their antiretroviral regimen.